Functional role of antibodies generated in heifers through immunization with Staphylococcus aureus vaccines in invasion and phagocytosis assays - Renna, María Sol; Pereyra, Elizabet Amanda Lorena; Baravalle, Celina; Camussone, Cecilia; Dallard, Bibiana Elisabet; Marcipar, Iván Sergio; Calvinho, Luis Fernando (2018)
A successful Staphylococcus aureus vaccine should elicit a long-term antibody response that prevents establishment of the infection. The aim of the present study was to evaluate the functional role of antibodies raised against different S. aureus CP5 vaccines in invasion to bovine mammary epithelial cells (MAC-T) and phagocytosis by bovine milk macrophages in vitro. Sera and whey from cows immunized with a whole-cell S. aureus CP5 vaccine adjuvanted with Al(OH)3 or with ISCOM Matrix, significantly reduced internalization of S. aureus in MAC-T cells without significant differences between both groups. The effect of antibodies generated by a S. aureus whole-cell and a lysate vaccine formulated with ISCOM Matrix was also evaluated. Sera and whey from both immunized groups significantly reduced S. aureus internalization in MAC-T cells without significant differences between both groups. Whey antibodies against whole-cell and lysate vaccines were also able to inhibit internalization in MAC-T cells of a heterologous S. aureus strain. In addition, sera from animals vaccinated with S. aureus lysate or bacterin promoted milk macrophage phagocytosis. These results provide an insight into the potential mechanisms by which these vaccines can afford protection to the mammary gland against S. aureus intramammary infection.